P-315 The importance of treatment features beyond pain reduction associated with gonadotropin-releasing hormone analogues from the patient perspective. (30th June 2022) - Maculaitis, M; Hunsche, E; Cislo, P; Ansani, N; Virro, J; Will, O; Peck, E; Kopenhafer, L; Olsen, P; Hauber, A; Beusterien, K; Kim, R
Abstract: Study question: Beyond reducing pain, how do women with moderate-severe-endometriosis pain prioritize treatment features and outcomes associated with gonadotropin-releasing hormone (GnRH) analogues? Summary answer: Moderate-severe-endometriosis patients prioritized safe long-term treatment, feeling treatment-effects within a few cycles, being able to maintain employment, reducing fatigue, depression, and headaches, and improving libido. What is known already: The importance of pain management in endometriosis treatment is well-established. Poor health-related quality of life has been attributed to endometriosis pain, with greater impact as the number of endometriosis symptoms and symptom severity increase. Endometriosis treatment options include analgesics for acute pain episodes and surgery in more severe cases, as well as hormone therapies, including GnRH analogues. The potential risks, benefits, and outcomes associated with currently available GnRH analogues for endometriosis treatment can vary. Data are lacking on the patient perspective with respect to potential treatment features and outcomes beyond just pain reduction. Study design, size, duration: Treatment-naïve patients with moderate-severe-endometriosis pain (rating scale ≥4 for menstrual pain) in the United States completed a cross-sectional online survey. Best-worst scaling (BWS) was used to assess preferences for key non-pain treatment attributes that were identified based on the literature. Cognitive pre-test interviews were conducted to confirm content validity of the questionnaire. Data collection for this ongoing survey was initiated in December 2021. Participants/materials, setting, methods: Patients (English-speaking, premenopausal, 18-50 years-old) were recruited via healthcare research panel. Eligible patients self-reported laparoscopy-confirmed-endometriosis, no endometriosis/other gynecological surgery in past 3 months, no osteoporosis/bone disease/uterine fibroids history, and healthcare coverage for previous 3 years. Treatment features in the BWS exercise included dosage flexibility, short treatment onset, reversibility of side effects, reducing fatigue, depression, headache, impact on libido, impact on sleep, ability to maintain employment, duration of treatment, and additional need for contraceptive use. Main results and the role of chance: Overall, 115 patients (31.1±7.5 years-old) were included in the analyses. On a 0 (no pain) to 10 (pain as bad as you can imagine) scale, the mean worst menstrual and non-menstrual pelvic pain (during past month) were 7.7±1.6 and 5.4±2.7, respectively. The most common endometriosis treatments ever used included over-the-counter pain medications (90.4%) and prescription contraceptives (74.8%). Of 11 BWS features tested, patients prioritized: "You can safely take the treatment for a long period of time" (relative importance=11.4%) "Your ability to get or maintain a job" (11.1%) "When starting a treatment, you will begin to feel the treatment's effects within the first few menstrual cycles" (10.9%) "You will be less depressed" (10.8%) "Your interest in sex will not be affected" (10.7%) "Any side-effects you may experience are resolved quickly after treatment stops" (10.1%) "You will be less fatigued or tired" (9.5%) "You will have fewer headaches or migraines" (8.6%) Least important to patients were: "Your sleep will not be affected" (6.8%) "Your doctor offers different options for the dose strength and how often you take it, as appropriate to your needs" (5.9%) "You are not required to take additional contraceptives along with the treatment" (4.0%) Limitations, reasons for caution: The preferences of patients who participated may differ from those who did not participate, thereby reducing the ability to generalize results. All data were self-reported; diagnosis and treatment could not be independently confirmed. The BWS exercise cannot include all possible attributes and outcomes relevant to patients. Wider implications of the findings: Beyond pain reduction, patients most highly valued having safe long-term treatment, feeling treatment effects within a few cycles, rapid resolution of side effects, being able to work, maintaining libido, and reducing fatigue, depression, and headaches. These factors can help physicians to better align endometriosis treatment decision-making with patient preferences. Trial registration number: Not applicable